Metaphysics, 9.8, 1050a30—b4: The Identity of Soul and Energeia - Shikiar, David Alan (Journal of Ancient Philosophy, 2015)
I argue that 1050a30—b3 contains an argument in which a series of analogies treating the ‘in’ relation are deployed to constrain how the relation between life and the soul is to be construed, such that, given other reasonable premises, it follows that the soul is identical with the activity life.  The interpretation of the ‘in’ relation turns crucially upon the distinction between a subject and a site for an activity, which opens the way for understanding the relation designated as not being that of inherence, which would imply some form of ontological distinction.  After establishing the conclusion concerning identity, I explain how the soul may be understood as possessing a modally graded internal structure, each higher-order modality corresponding to a higher level of completion, thinking being the highest grade in human beings.  I then show how the identity of soul and living activities affirmed at b2—3 implies the substantial priority of energeia to potentiality affirmed at b3—4.